2022
DOI: 10.1177/26349833221087755
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydroxyapatite on physical, mechanical, and morphological properties of starch-based bio-nanocomposite films

Abstract: In this research, nanocomposite films based on starch were developed with the addition of hydroxyapatite nanoparticles as a mineral filler. Hydroxyapatite was synthesized by a chemical method using calcium nitrate and diammonium hydrogen phosphate. Various concentrations of hydroxyapatite nanoparticles were mixed with starch, and the developed films were evaluated in terms of physical, mechanical, and morphological properties. The highest values of mechanical parameters (tensile strength and elongation at brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Figure 3 shows pure PS and PC without hydroxyapatite, and it is shown that the intensity is very low, with broad peaks indicating the amorphous nature of the polymer. With the addition of hydroxyapatite with a concentration of 1.6 wt.%, the intensity increases, and the composite becomes crystalline, which leads to higher mechanical properties, as seen in the results; these results agree with [25].…”
Section: Figure 3 Xrd Patterns Of the Melt Casting Pc Ps And Pc/ps Bl...supporting
confidence: 86%
See 1 more Smart Citation
“…Figure 3 shows pure PS and PC without hydroxyapatite, and it is shown that the intensity is very low, with broad peaks indicating the amorphous nature of the polymer. With the addition of hydroxyapatite with a concentration of 1.6 wt.%, the intensity increases, and the composite becomes crystalline, which leads to higher mechanical properties, as seen in the results; these results agree with [25].…”
Section: Figure 3 Xrd Patterns Of the Melt Casting Pc Ps And Pc/ps Bl...supporting
confidence: 86%
“…It is seen that the tensile properties have been hermetically decreased by the increase of hydroxyapatite concentration due to the agglomeration formation during the processing of composite above 1.6 wt% hydroxyapatite in PC/PS; the main reason behind this is hydroxyapatite content reduces hydrogen bonds formation and its effect is higher than crosslink bonds formation, which decreases the tensile strength and the elongation at break, these results agree with [25].…”
Section: Mechanical Propertiessupporting
confidence: 82%
“…Furthermore, in dry conditions, HAp addition reduced (~20%) the maximum probe displacement through the biomembranes. According to Hadi et al, 22 HAp addition to starch matrixes increases the tensile strength because the load is transferred to the polymer matrix/nanoparticle interface. On the other hand, in wet conditions, the presence of HAp did not affect the maximum probe displacement through the biomembranes.…”
Section: Resultsmentioning
confidence: 99%
“…[17][18][19] Nanoparticle addition can modify starch biomembranes, to improve their mechanical and biomedical properties. [20][21][22] For instance, hydroxyapatite nanoparticles (HAp) have been widely studied as a biocompatible and osteoconductive biomaterial because they chemically resemble biological apatite. 23 However, tissue replacement and load-bearing applications of HAp have been limited since handling the particles at defective sites with complex shapes is difficult.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation